THE DIAGNOSTIC VALUE OF COMPUTED TOMOGRAPHY IN THE DIAGNOSIS OF COVID-19 DISEASE - Saidolim Murodkosimov; Sevginoz Zhamshedovna Khodzhieva; Abdumurodov Mirjakhon Bahriddin Ugli; Ochilov Okhunzhon Odil ugli; Abdusalomov Mansur Dilshodovich (Scholar Express Journals, 2022)
A new coronavirus infection (COVID-19) has caused a pandemic, which not only caused a revision of approaches to diagnosis and treatment of infectious diseases, but also required a reassessment of the role of diagnostic radiology in detecting COVID-19 and its complications, assessing the effectiveness of current treatment, and verifying manifestations of postvaccination syndrome. Undoubtedly, special attention at primary diagnosis of the disease is paid to the state of lungs, and more and more data indicate the involvement of gastrointestinal tract organs, other target organs. Obviously, it is computed tomography (CT) that forms the basis of the radiotherapy diagnosis of COVID-19. However, the need to control the radiation load on the patient's body, the relative focus of chest CT assessment on changes in the lungs only, insufficient use of quantitative criteria of lung and abdominal organs examination are the reasons for optimizing algorithms of disease diagnosis, CT technique and assessment of obtained results.
Keywords: COVID-19; coronavirus pneumonia; multislice computed tomography